The use of abbreviations by superscript letter in an early fifteenth-century manuscript of the Wycliffite Bible - Grzybowska, Joanna (LingBaW. Linguistics Beyond and Within, 2018)
The use of scribal abbreviations in medieval manuscripts was mainly dictated by the need to save space and time as the creation of a medieval book was both extremely costly and time-consuming. One of the types of scribal abbreviations used in medieval manuscripts is abbreviation by superscript letter. In this type of abbreviations one superscript letter indicates the ending of a given word, or, in some cases, a medial position. Both vowels and consonants were used as abbreviations by superscript. They usually denoted, apart from the actual letter written in superscript, the preceding vowel or the letter <r>. According to Cappelli (1929/1982), superscript letters in Latin were used mainly in word-final positions; however, it was not uncommon for a superscript vowel to appear word-medially. The main objective of this paper is to investigate the use of superscript letters in an early fifteenth-century manuscript of the Wycliffite Bible (Mscr.Dresd.Od.83) on the basis of the Gospel of Matthew. Within the manuscript there are both superscript consonants and vowels. However, in some cases these abbreviations seem to appear in very specific contexts, whereas in other cases the contexts allowing the abbreviations to appear are much broader. The possible reasons behind this situation will be discussed within this paper along with the correspondence between the superscript letter and the spelling conventions used within the manuscript.